Depth, degrees and tectonic settings of mantle melting during craton formation: Inferences from major and trace element compositions of spinel harzburgite xenoliths from the Udachnaya kimberlite, central Siberia - Doucet, Luc-Serge; Ionov, D.; Golovin, A.; Pokhilenko, N. (Elsevier BV, 2012)
We examine major and trace element compositions of whole-rocks and minerals of 18 spinel harzburgite xenoliths from the Udachnaya kimberlite in the central Siberian craton. The samples are fresh, modally homogeneous and large enough to provide representative whole-rock samples ( > 100. g); all residual spinel peridotites in our collections that satisfied these criteria were selected for this study. Their Mg# ranges from 0.92 to 0.93. Thirteen xenoliths have 6-22% orthopyroxene (opx) and 0-3% clinopyroxene (cpx); five are opx-rich (31-43%) and contain 3-5% cpx. The low-opx Udachnaya harzburgites define regular co-variation trends on major and minor oxide plots and appear to be pristine melt extraction residues. Their Al-Fe and Al-Mg# trends, in combination with experimental results on melting of fertile peridotites, indicate an origin by ~40% of polybaric decompression fractional melting between 7-4. GPa and =1-2. GPa. In line with Cr and HREE abundances, garnet was stable in the residues at early melting stages. Thus, the spinel facies cratonic peridotites situated at > 40 to 130. km (1-4. GPa), are residues of melting that took place over a broader depth range; the residues probably underwent density-driven segregation from the denser ambient mantle to form the base of cratonic nuclei. The opx-rich Udachnaya harzbrugites cannot be produced by dry or hydrous melting at 1-7. GPa and might be related to fractionation or metamorphic segregation of initial high-P melting residues and their interaction with interstitial liquids retained in the residues during gravity-driven upwelling. Our results, in comparison with published data on arc and fore-arc peridotites, show no evidence that significant enrichments in silica (opx) could be produced during melting or metasomatism in subduction settings, or that initial melting residues were dunites, which were later transformed to harzburgites by melt-rock reactions. © 2012 Elsevier B.V.